2022
DOI: 10.3389/fphys.2022.863217
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Atrial Remodeling in Female Amateur Marathon Runners Assessed by Three-Dimensional and Speckle Tracking Echocardiography

Abstract: Endurance athletes have an increased risk of atrial remodeling and atrial arrhythmias. However, data regarding atrial adaptation to physical exercise in non-elite athletes are limited. Even less is known about atrial performance in women. We aimed to elucidate exercise-induced changes in atrial morphology and function in female amateur marathon runners using three-dimensional (3D) echocardiography and two-dimensional (2D) speckle tracking echocardiography (STE). The study group consisted of 27 female (40 ± 7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A recent study conducted on female amateur marathon runners investigated the remodeling of the cardiac chambers induced by endurance training, which might be different from that of male athletes [95]. The authors [95] found that immediately after a marathon there was a significant, but reversible, dilation of both the right atrium and the right ventricle, accompanied by a decrease in the contractility of the right ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted on female amateur marathon runners investigated the remodeling of the cardiac chambers induced by endurance training, which might be different from that of male athletes [95]. The authors [95] found that immediately after a marathon there was a significant, but reversible, dilation of both the right atrium and the right ventricle, accompanied by a decrease in the contractility of the right ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted on female amateur marathon runners investigated the remodeling of the cardiac chambers induced by endurance training, which might be different from that of male athletes [95]. The authors [95] found that immediately after a marathon there was a significant, but reversible, dilation of both the right atrium and the right ventricle, accompanied by a decrease in the contractility of the right ventricle. In contrast, the left heart chambers were less affected by acute remodeling: the size of the left ventricle had decreased after the race and no significant reduction in the size of the left atrium was observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain such changes only by an increase in the afterload. Some similarities can be found with an athlete’s heart in which atrial remodeling is a physiological adaptation to volume overload allowing for greater volume delivery and increased cardiac output ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, discrepancies exist among different studies concerning the acute effects of intense exercise on atrial function. Even if prolonged exercise can cause acute atrial dysfunction, preliminary evidence suggests that this is a transient and reversible effect [ 20 ].…”
Section: Acute Effectsmentioning
confidence: 99%